Land Use Change Prediction In Dhaka City Using Gis Aided Markov Chain Modeling - Islam, Md Shahidul; Ahmed, Raquib (Journal of Life and Earth Science, 2012)
The main objective of this paper is to evaluate the land use change in Dhaka City based on the need and purpose to predict future scenario of Dhaka City. Dhaka being a mega city has been challenged by numerous difficulties like unplanned urbanization, traffic congestion, water logging etc. Land use classification and analysis is performed using a GIS and Remote sensing technique, and GIS aided ‘Markov Cellular Automata’ technique is used to model the land use change. Based on the past trend (from 1991 to 2008) of land use changes, the future land use map of Dhaka city for the year of 2020 and 2050 has been generated. And collected maps and images were sorted and classified for analysis and interpretation. Landsat TM image of 1991 and Google image of 2008 were employed in this study to produce land use classification based on Anderson modified version method. IDRISI, Land Change Modeler (LCM) was used to analyze the land use/cover changes between various classes during the period 1991-2008. It is assumed that this kind of research will contribute to shaping the urban form of the city in a planned manner. So, that Dhaka can be a much more livable and planned city in near future. DOI: http://dx.doi.org/10.3329/jles.v6i0.9726 JLES 2011 6: 81-89